2019
DOI: 10.15252/embr.201846331
|View full text |Cite
|
Sign up to set email alerts
|

Clipped histone H3 is integrated into nucleosomes ofDNAreplication genes in the human malaria parasitePlasmodium falciparum

Abstract: Post‐translational modifications of histone H3 N‐terminal tails are key epigenetic regulators of virulence gene expression and sexual commitment in the human malaria parasite Plasmodium falciparum . Here, we identify proteolytic clipping of the N‐terminal tail of nucleosome‐associated histone H3 at amino acid position 21 as a new chromatin modification. A cathepsin C‐like proteolytic clipping activity is observed in nuclear parasite extracts. Notably, an ectopically expressed version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In a recent study, we have shown that the replication protein PfORC2 goes through an ER-associated proteolytic processing pathway to attain its mature form (Sharma et al, 2018). Another study on histone H3 shows that PfH3 protein is 'clipped' by a nuclear protease in asexual blood stage and this cleaved H3 form is enriched at the upstream regions of few DNA replication/repair genes (Herrera-Solorio et al, 2019). However, cleaving of a nuclear protein by a food vacuole protease is unique to parasites and does not generally occur in eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we have shown that the replication protein PfORC2 goes through an ER-associated proteolytic processing pathway to attain its mature form (Sharma et al, 2018). Another study on histone H3 shows that PfH3 protein is 'clipped' by a nuclear protease in asexual blood stage and this cleaved H3 form is enriched at the upstream regions of few DNA replication/repair genes (Herrera-Solorio et al, 2019). However, cleaving of a nuclear protein by a food vacuole protease is unique to parasites and does not generally occur in eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria pathogens rely on multiple layers of epigenetics in order to regulate gene expression across their complex life cycle (for review, see reference 2 ). This fast-evolving research field has recently revealed several unprecedented epigenetic mechanisms in P. falciparum such as histone clipping ( 3 ), the role of noncoding RNAs in regulating virulence gene expression and sexual commitment ( 4 , 5 ) as well as the role of the RNA exosome-linked RNase (Rrp6) in ncRNA decay regulation ( 6 ). Furthermore, the detection of an unusual DNA cytosine modification has been recently linked to P. falciparum gene expression ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cleavage activity is induced under conditions of nutrient deprivation and sporulation ( Santos-Rosa et al , 2009 ). In the human parasite Plasmodium falciparum , H3 clipping occurs after Ala21 and is abundant in genes regulating DNA replication of the pathogen ( Herrera‐Solorio et al , 2019 ). H3 cleavage was also observed in vertebrates where it is cell type-dependent and plays multiple important biological functions ( Azad et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%